Adsorption Condition of Geopolymer Synthesized from Corncob Ash Using NaOH and NaSiO for Methylen Blue Removal - Wardhani, Gladys Ayu Paramita Kusumah; Yahya, Amri (Sains Natural: Journal of Biology and Chemistry, 2025)
In this study, geopolymer G10 based corncob ash were synthesized by alkaline activation using NaOH 10 M-Na2SiO3(2:1) with ratio 5:3. The G10 were characterized by X-Ray fluorescence (XRF) and Fourier transform infrared spectroscopy (FTIR) and applied to methylene blue adsorptiom in an aqueous media  in batch method. Adsorption efficiency were observed in optimum pH, contact time, adsorbent weight, and methylene blue concentration using UV-Visible spectrophotometer. The resulting geopolymer is brown at a drying temperature of corncob powder at 80 ℃. Based on the XRF results, the Si:Al ratio value in corncob ash was 3:1. The bonds in the geopolymer include, Si-O-Si, Si-O-Al, Si-OH, and Al-O-Si. Optimum adsorption conditions were obtained at pH 3, contact time at 120 menit, adsorben weight is 50 mg, and initial concentration of methylene blue is 200 mg/L.